2019
DOI: 10.3389/fneur.2019.01151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epileptic Spiking Associated With Brain Amyloidosis in APP/PS1 Mice

Abstract: Epileptic activity without visible convulsions is common in Alzheimer's disease (AD) and may contribute adversely to the disease progress and symptoms. Transgenic mice with amyloid plaque pathology also display epileptic seizures, but those are too infrequent to assess the effect of anti-epileptic treatments. Besides spontaneous seizures, these mice also display frequent epileptic spiking in epidural EEG recordings, and these have provided a means to test potential drug treatment to AD-related epilepsy. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 42 publications
4
62
0
Order By: Relevance
“…Hippocampal hyperactivity is observed in Aβ positive MCI patients, which persists with disease progression despite increasing rates of hippocampal atrophy and dementia scale ratings 9 . Elevated hippocampal activity has also been reported in several mouse models of AD with progressive amyloidosis 24 28 . These changes in neuronal networks are initially observed in mice before plaque deposition 29 , 30 , supporting a role for soluble Aβ in neuronal hyperactivity.…”
Section: Discussionmentioning
confidence: 81%
“…Hippocampal hyperactivity is observed in Aβ positive MCI patients, which persists with disease progression despite increasing rates of hippocampal atrophy and dementia scale ratings 9 . Elevated hippocampal activity has also been reported in several mouse models of AD with progressive amyloidosis 24 28 . These changes in neuronal networks are initially observed in mice before plaque deposition 29 , 30 , supporting a role for soluble Aβ in neuronal hyperactivity.…”
Section: Discussionmentioning
confidence: 81%
“…Several lines of evidence suggest that hyperexcitability is a contributing factor, primarily in familial AD (Chin and Scharfman, 2013; Friedman et al, 2012; Ghatak et al, 2019; Noebels, 2011; Nygaard et al, 2015; Palop et al, 2007; Palop and Mucke, 2009; Palop and Mucke, 2010; Petrache et al, 2019; Siskova et al, 2014; Styr and Slutsky, 2018; Verret et al, 2012; Vossel et al, 2013; Vossel et al, 2017). Hyperexcitability is manifested by intermittent seizures or epileptiform activity in an electroencephalogram (EEG) (Chin and Scharfman, 2013; Friedman et al, 2012; Gureviciene et al, 2019; Noebels, 2011; Nygaard et al, 2015; Palop et al, 2007; Palop and Mucke, 2009; Palop and Mucke, 2010; Verret et al, 2012; Vossel et al, 2013; Vossel et al, 2017). The seizures are easily missed because they are not always accompanied by movement, and epileptiform activity is easily missed because an EEG is not always conducted, or recordings are made far from the site of abnormal activity (Lam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…No EEG study on AD patients to our knowledge has discovered SWDs, but so far only a couple of studies have more in detail described examples of any kind of nonconvulsive epileptic spiking in AD patients 2,52 . In contrast, two independent research groups have found substantial overrepresentation of SWDs in APP/PS1 mice compared wild-type littermates while the number of single cortical spikes did not differ between the genotypes 19,53 and a recent study reported an eightfold higher occurrence of SWDs in APP/PS1 transgenic rats than in wild-type littermates 54 . Together, these findings suggest that SWDs are closely linked to brain amyloidosis.…”
Section: Discussionmentioning
confidence: 75%